The solution of the robust feedback synthesis problem for a canonical system - Korobov, V. I.; Revina, T.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The problems of the global and local robust feedback syntheses of a bounded control for a system with unknown bounded perturbation are considered. Our approach is based on the controllability function method suggested by V.I. Korobov. We have found the largest segment, where the perturbation can vary, and have given a positional control, which steers an arbitrary initial point to the origin in some finite time for any admissible perturbation from this segment. An estimate of the time of motion from an initial point to the origin has been given.